High-risk situations of inclinations to relapse among former drug addicts: a descriptive analysis - Razali, Asbah; Madon, Zainal (Human Resource Management Academic Research Society, 2021)
Although the government has carried out countless efforts to prevent relapse among drug addicts after receiving treatment, the increasing rate of relapsed addicts still remains at a worrying level. To this day, the country bears a high cost to treat and rehabilitate former drug addicts. This study aims to identify the levels of inclination of relapse based on eight high-risk situations usually faced by former addicts. This study involved 242 former drug addicts that completed the treatment and rehabilitation period, utilizing the Inventory of Drug-Taking Situations instrument (IDTS) by Annis and Martin (1985). The findings show the inclination to relapse among former addicts are at a high level for all high-risk situation dimensions. This means the participating respondents are at a high-risk of relapse. Therefore, in their efforts to combat the problem of relapse, the National Antidrug Agency (AADK) and the Cure and Care Rehabilitation Centre (CCRC) must take into account risk factors that contribute to relapse among addicts, and then adopting them as a guideline to further strengthen strategies to combat this problem in the future.